The Role of Human Resource Practices in Creating Organizational Competitive Advantage – Elucidate Employee Satisfaction through Intervention Programme - Swathi Kumari, Gajanethi (International Journal of Psychosocial Rehabilitation, 2019)
An organization’s HR is fragile, relationships are delicate, contributions are unpredictable and stability is uncertain. Thus, it provides a great challenge and opportunity to the organization Government of India, as part of its national agenda to promote growth, increase in efficiency and international competitiveness, has been continuously framing policies for industrial growth, fiscal, trade and foreign investment to achieve overall socioeconomic development of the country. Private sector plays a dominant role for generating employment opportunities inside the country. A huge number of large scales, small scale, cottage scale units are under the control of private sector. An attempt has been made to analyze the public and private organizations of which the HR Practices became the special focus of the investigation reason to study the HR practices was because of globalization there has been migration, heavy trafficking across seas and continents with continues communication, which resulted in human beings got placed in different countries with different climates, different cultures, different lifestyles etc. Hence, studying HR practices was undertaken to assess whether the practices are going along with changing times. The satisfaction level of the employees were identified and intervention program was conducted for dissatisfied employees and communicated through special lectures related to Work-Life balance, peace, stress management, etc.,